Derivation of a test for measuring degree of environmental education - Pohorille, Ralph Leon (Not Specified, 2024)
The need to derive a test for measuring degree of environmental education in the South African context was perceived. A test aimed at standard 6- pupils was devised based on three components: knowledge, feeling and action. Three item pools were developed and scrutinised by panels of experts and a pilot test was formulated. The results of the pilot test were analysed statistically and the test refined into a shorter, final test which was found to be both reliable and valid. This final test was implemented with a sample population of some 300 pupils and was found to discriminate between those who are environmentally educated and those who are not. Several uses of the test are suggested. An attempt to use teacher judgement as an independent means of identifying environmentally educated pupils was not iuccessful.